Liability for Violation of the Obligation of Care in the Criminal Code of the Republic of Poland - Zaytsev, Oleksiy; Pavshuk, Kateryna (Problems of legality, 2024)
The problem of non-fulfilment or improper fulfillment by parents (persons who replace them) of childcare responsibilities exists in all countries, regardless of the form of government, state system, and income level of the population. Ukraine has been in the process of integration with the European Union for a long time, so it is useful to study the foreign legislative approach to the regulation of responsibility for the violation of these obligations. The purpose of the article is to study the Polish experience of establishing criminal liability for non-fulfilment of child care obligations. In the research dogmatic, systemic-structural, statistical, historical-legal, formal-legal methods were used. Attention is paid to the legislation of the Republic of Poland, which provides for the right and duty of parents to care for and raise children. The genesis of the criminal law regarding responsibility for violation of these duties in the Criminal Code of 1932, 1969, and 1997 is given. Statistical data on the number of criminal proceedings and persons convicted of this criminal offense (2009–2020) are summarized. The peculiarities of the structure of the crime composition provided for in Art. 210 of the Criminal Code of the Republic of Poland were studied; objective and subjective signs. The analysis was carried out on the basis of the doctrine of Polish criminal law and the practice of courts of general jurisdiction, in particular the Supreme Court of the Republic of Poland. The practice of the Constitutional Tribunal of the Republic of Poland was used. Based on the results of the research, conclusions were formulated regarding objects of criminal law protection; objective and subjective side and subject composition. The differentiation of criminal liability in case of causing death to the victim was noted. The legislator also provided in cases of this crime the possibility of notifying the competent family court about the expediency of deprivation or limitation of parental or guardian rights in case of committing a crime to the detriment of a minor or in complicity with him. The separation of an independent structural section (subsection) in the Criminal Code of Ukraine, which includes criminal offenses against the family, as well as the improvement of criminal legal measures against persons who have committed such crimes, is supported.